2021
DOI: 10.21203/rs.3.rs-905429/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence and risk factors for hypoglycemia in patients with hepatocellular carcinoma

Abstract: AimTo evaluate the incidence and risk factors for hypoglycemia in patients with hepatocellular carcinoma (HCC).MethodsWe collected and analyzed the clinical data of patients with HCC in our cancer center between April 2020 and June 2021. Univariate and multivariate logistic regression analyses were performed to identify the risk factors associated with hypoglycemia.ResultsThe incidence rate of hypoglycemia in patients with HCC was 28.9% (67/232). Multivariate logistic regression analysis showed a significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless, hypoglycemia is more likely to develop in massive hepatocytes necrosis. A study in China suggested that Child-Pugh grade C, higher AFP, and low HbA1c significantly increase the likelihood of hypoglycemia in the population (Zheng et al, 2021). In this case, the absence of chronic liver disease stigmata with a normal albumin and coagulation blood test have put the patient in a compensated liver state.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, hypoglycemia is more likely to develop in massive hepatocytes necrosis. A study in China suggested that Child-Pugh grade C, higher AFP, and low HbA1c significantly increase the likelihood of hypoglycemia in the population (Zheng et al, 2021). In this case, the absence of chronic liver disease stigmata with a normal albumin and coagulation blood test have put the patient in a compensated liver state.…”
Section: Discussionmentioning
confidence: 99%